2017
DOI: 10.1002/glia.23141
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate induces Ca2+signaling and CXCL1 release via TRPC6 channel in astrocytes

Abstract: A biologically active lipid, sphingosine-1-phosphate (S1P) is highly abundant in blood, and plays an important role in regulating the growth, survival, and migration of many cells. Binding of the endogenous ligand S1P results in activation of various signaling pathways via G protein-coupled receptors, some of which generates Ca mobilization. In astrocytes, S1P is reported to evoke Ca signaling, proliferation, and migration; however, the precise mechanisms underlying such responses in astrocytes remain to be el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
(69 reference statements)
0
26
0
Order By: Relevance
“…MAPK signal pathway is implicated in inflammatory response induced by oxidative stress 31 . Furthermore, previous studies show relationships between the activation of TRPC6 and MAPK signals, which seemed to be context-dependent 47,48 . Here, we found that treatments with H 2 O 2 or O 3 evoked the release of inflammatory factors IL-6 and IL-8 via activating MAPKs (ERK, p38, JNK) (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…MAPK signal pathway is implicated in inflammatory response induced by oxidative stress 31 . Furthermore, previous studies show relationships between the activation of TRPC6 and MAPK signals, which seemed to be context-dependent 47,48 . Here, we found that treatments with H 2 O 2 or O 3 evoked the release of inflammatory factors IL-6 and IL-8 via activating MAPKs (ERK, p38, JNK) (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…TRPC6 has been shown to make a complex with TRPC3 in neuronal cells and prostate cancer epithelial cells. In astrocytes, sphingosine 1-phosphate (S1P)-evoked secretion of the C-X-C motif chemokine ligand 1 (CXCL1) is mediated through activation of TRPC6 and the mitogen-activated protein kinase (MAPK) signaling pathway [76]. Furthermore, TRPC6 is important in transforming growth factor β1 (TGFβ1) signaling in vascular smooth muscles.…”
Section: Trpc6mentioning
confidence: 99%
“…Western blotting was performed as described previously [42], with slight modification. After 2 days in enriched culture, cells were lysed in RIPA buffer (Nacalai Tesque).…”
Section: Western Blottingmentioning
confidence: 99%